2011
DOI: 10.1890/10-0465.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant–soil feedbacks in driving native-species recovery

Abstract: The impacts of exotic plants on soil nutrient cycling are often hypothesized to reinforce their dominance, but this mechanism is rarely tested, especially in relation to other ecological factors. In this manuscript we evaluate the influence of biogeochemically mediated plant-soil feedbacks on native shrub recovery in an invaded island ecosystem. The introduction of exotic grasses and grazing to Santa Cruz Island, California, USA, converted native shrublands (dominated by Artemisia californica and Eriogonum arb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 41 publications
3
54
2
1
Order By: Relevance
“…The strength of this effect will ultimately depend on the relative importance of other limiting factors that can influence abundance and persistence, such as competition, dispersal limitation and herbivory [2,13]. All of these factors have been shown to constrain native plant performance in this system [58 -61], such that the net strength of the conspecific feedbacks could be relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of this effect will ultimately depend on the relative importance of other limiting factors that can influence abundance and persistence, such as competition, dispersal limitation and herbivory [2,13]. All of these factors have been shown to constrain native plant performance in this system [58 -61], such that the net strength of the conspecific feedbacks could be relatively weak.…”
Section: Discussionmentioning
confidence: 99%
“…Invasion can further interact with other drivers of global change such as N deposition, as discussed above. Moreover, some studies have reported that the effects of plant invasion on soil facilitate further invasion by the initial invasive species or by other species (Allison and Vitousek, 2004;Sharma and Raghubanshi, 2009), although not all studies provide clear results on this topic (Yelenik and Levine, 2011). Thus, alien success in nutrient-rich soils is related to higher growth rates, low C-N and C-P ratios, fast plasticity in resource acquisition capacity and high reproductive investment; in nutrient-poor soils, high invasive success is related to conservative use of resources including nutrients.…”
Section: Impacts Of Plant Invasion On the Availability And Stoichiomementioning
confidence: 99%
“…Invasion success has also been considered in the light of plant-soil feedbacks (Packer & Clay 2000;Klironomos 2002;Bever et al 2010;Yelenik & Levine 2011;Suding et al 2013). The potential complexity of these feedbacks is shown in the case of the invasive nitrogen (N)-fixing tree Robinia pseudoacacia L. (Callaway et al 2011).…”
Section: Invasionmentioning
confidence: 99%